Peptide Deformylase: A New Target in Antibacterial, Antimalarial and Anticancer Drug Discovery - N. Sangshetti, Jaiprakash; Kalam Khan, Firoz A.; B. Shinde, Devanand (Current Medicinal Chemistry, 2015)
Peptide deformylase (PDF) is a class of metalloenzyme responsible for catalyzing the removal of the N-formyl group from N-terminal methionine following translation. PDF inhibitors are moving into new phase of drug development. Initially, PDF was considered as an important target in antibacterial drug discovery; however genome database searches have revealed PDF-like sequences in parasites (P. falciparum) and human, widening the utility of this target in antimalarial and anticancer drug discovery along with antibacterial. Using structural and mechanistic information together with high throughput screening, several types of chemical classes of PDF inhibitors with improved efficacy and specificity have been identified. Various drugs like, GSK-1322322 (Phase II), BB-83698 (Phase I), and LBM-415 (Phase I) have entered into clinical developments. Developments in the field have prompted us to review the current aspects of PDFs, especially their structures, different classes of PDF inhibitors, and molecular modeling studies. In nut shell, this review enlightens PDF as a versatile target along with its inhibitors and future perspectives of different PDF inhibitors.
Keywords: antimalarial